SISTEM INFORMASI ANALISIS PLAYER TOURNAMENT MOBILE LEGENDS BERBASIS WEB PBESI MAJALENGKA - Agung Pamungkas, Bayu; Zaliluddin, Dadan (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
This research is motivated by the increasing number of E-Sports users or enthusiasts worldwide, as E-Sports has become an integral part of official sports competitions. Therefore, by creating an information system to process the data from Mobile Legends tournaments, the aim is to make informed decisions in identifying potential athletes who can bring honor to their region or country. In conclusion, this system is developed to provide support for decision-making, provide information related to the E-Sports organization that oversees the E-Sports ecosystem, namely the Indonesian Esports Association (PBESI), and offer prediction features to estimate the likelihood of victory for each player in the competition